The Reception of John Locke’s Writings at Christ Church, Oxford, c. 1690–1800 - Chatterjee, Jacob Donald (Locke Studies, 2023)
This article presents some overlooked evidence on the reception of John Locke’s writings at Christ Church, Oxford. It is intended to supplement a new article in the History of Universities on the surprisingly positive response to Locke’s Essay Concerning Human Understanding (1689) at that bastion of late seventeenth-century high churchmanship. This evidence sheds new light on: the reception of Epicureanism at that college in the 1650s; Locke’s personal connections at Christ Church; book-holdings of Locke’s writings at the early eighteenth-century college; some unnoticed uses of Locke’s writings by members of Christ Church; the European and North American reception of one Christ Church Lockean; and, the changing trajectory of the later eighteenth-century reception of Locke at that college.